A Trans-Species Missense SNP in Amhr2 Is Associated with Sex Determination in the Tiger Pufferfish, Takifugu rubripes (Fugu) - Kamiya, Takashi (Public Library of Science, 2012)
Heterogametic sex chromosomes have evolved independently in various lineages of vertebrates. Such sex chromosome pairs often contain nonrecombining regions, with one of the chromosomes harboring a master sex-determining (SD) gene. It is hypothesized that these sex chromosomes evolved from a pair of autosomes that diverged after acquiring the SD gene. By linkage and association mapping of the SD locus in fugu (Takifugu rubripes), we show that a SNP (C/G) in the anti-Müllerian hormone receptor type II (Amhr2) gene is the only polymorphism associated with phenotypic sex. This SNP changes an amino acid (His/Asp384) in the kinase domain. While females are homozygous (His/His384), males are heterozygous. Sex in fugu is most likely determined by a combination of the two alleles of Amhr2. Consistent with this model, the medaka hotei mutant carrying a substitution in the kinase domain of Amhr2 causes a female phenotype. The association of the Amhr2 SNP with phenotypic sex is conserved in two other species of Takifugu but not in Tetraodon. The fugu SD locus shows no sign of recombination suppression between X and Y chromosomes. Thus, fugu sex chromosomes represent an unusual example of proto–sex chromosomes. Such undifferentiated X-Y chromosomes may be more common in vertebrates than previously thought.